Traders and Trade in Colonial Ovamboland, 19251990 : Elite Formation and the Politics of Consumption under Indirect Rule and - Dobler, Gregor (Book collections on Project MUSE., 2014)
Taking the history of trade and of traders as its subject matter, this book offers the first economic history of northern Namibia during the twentieth century. It traces Namibia's way from a rural, largely self-relying society into a globalised economy of consumption. This transformation built on colonial economic activities, but it was crucially shaped by local traders, a new social elite emerging during the 1950s and 1960s. Becoming a trader was one of the few possibilities for black Namibians to gain monetary income at home. It was a pathway out of migrant labour, to new status in the local.